TINJAUAN HUKUM ISLAM TENTANG MAJA TOMATOA DALAM KONFLIK RUMAH TANGGA - Sukaina, Andi; Bahri, Andi Syamsul; Khair, Abul (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2025)
This article discusses the Islamic legal perspective on the relationship between parents-in-law and children-in-law, as well as the factors causing conflict in household life, particularly in Arasoe Village, Cina District, Bone Regency. In Islamic law, a son-in-law becomes a mahram to his mother-in-law after a lawful marriage to her daughter, making marriage between them permanently forbidden even if the marriage later ends. Despite this mahram status, Islam emphasizes the importance of maintaining proper conduct, observing boundaries of modesty (aurat), and upholding politeness in interactions. A son-in-law is obliged to treat his parents-in-law with kindness as he would his own parents, and likewise, parents-in-law are encouraged to treat their children-in-law as their own children. This study also reveals factors contributing to conflicts between parents-in-law and children-in-law, including poor communication, economic problems, and work-related pressures that affect household harmony. Additionally, the concept of Maja Tomatoa in Bugis culture is understood as a satirical term referring to parents-in-law who excessively interfere in their children’s household affairs. Both Islam and Bugis culture emphasize that the role of parents should be that of wise advisors rather than controllers. Therefore, conflict resolution is expected to be achieved through mutual understanding, maintaining proper conduct, and upholding the values of Islamic teachings and local wisdom.